1995
DOI: 10.1055/s-2007-972996
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Dosages of Caffeine on Endurance Performance Time

Abstract: 995.Accepted aftel revision: 0ctober 30, 1994 &t+J*$Bãi The effect of dlfferent dosa ges of caffelne (0 -5 -9 -13 mg 'l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
159
4
17

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(195 citation statements)
references
References 3 publications
14
159
4
17
Order By: Relevance
“…These improvements are comparable to those reported by others (6,20,28,33) who have used a similar mode and intensity of exercise, as well as a similar dose of caffeine ingested 1-1.5 h before exercise. Furthermore, our findings 3 h after ingestion are consistent with a previous study by Flinn et al (12).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These improvements are comparable to those reported by others (6,20,28,33) who have used a similar mode and intensity of exercise, as well as a similar dose of caffeine ingested 1-1.5 h before exercise. Furthermore, our findings 3 h after ingestion are consistent with a previous study by Flinn et al (12).…”
Section: Discussionsupporting
confidence: 89%
“…habits (5,8,12,19,28,32). Two studies from the same laboratory report equivocal findings after a 9 mg/kg dose of caffeine (19,32), and Graham and Spriet (19) have suggested that these inconsistent effects reflect the different proportions of users and nonusers or light consumers of caffeine in their subject groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Caffeine (1,3,7-trimethylxantine) is the most commonly consumed social drug in western society for increased physical and cognitive performance [1][2][3][4][5], and it is the main ergogenic resource used by athletes [6]. Initially controversial, caffeine was banned by the International Olympic Committee from 1980-2003 [1,6,7], but then in 2004 its use was approved by the World Anti-doping Agency (WADA), and later this year by the U.S. Anti-doping Agency (USADA; 2016).
…”
mentioning
confidence: 99%
“…The ergogenic effects of caffeine have been demonstrated in different sport modalities, namely running [8,9], cycling [10,11], rowing [12], track and field [3], team sports [4], and martial arts [13], among others.…”
mentioning
confidence: 99%